The Effect of Work Motivation and Discipline on the Performance of Contract Employees at PT. Astra International Palembang - Muhammad Iqbal Ramadhan; Susi Handayani; Meilin Veronica (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine the effect of motivation and work discipline on employee performance at PT. Astra International Tbk plaju palembang. This type of research was quantitative research. The analysis in this research utilized Multiple Linear Regression analysis. The results of this study indicate that there is a significant influence of motivation and work discipline on the performance of contract employees at PT. Astra International Tbk Plaju Palembang. The results of this study are expected to provide benefits for companies to evaluate the performance of contract employees through increasing motivation and work discipline.